The Role of Authentic Leadership in Improving the Quality of Work Life - Jaber Fzaea, Amal; Yousef Odhafa, Raed (Iraqi Journal for Administrative Sciences, 2025)
This study aims to analyze the impact of authentic leadership dimensions (self-awareness, relational transparency, balanced processing, ethical perspective) on the quality of work life (working conditions, life balance, professional growth, reward system, participation) among employees at the College of Administration and Economics - Sumer University, in light of increasing organizational pressures and the declining effectiveness of traditional leadership styles. The study adopted the descriptive analytical approach, using a questionnaire prepared based on approved standards, and distributed to a sample of (80) employees. The data were analyzed using appropriate statistical methods via SPSS v.26, including averages, standard deviations, and regression analysis. The results showed a statistically significant impact for each dimension of authentic leadership on the quality of work life, confirming the effective role of this leadership style in enhancing the university work environment. The study recommends adopting authentic leadership as a strategic approach to improving the quality of work life and raising the efficiency of institutional performance.